2003
DOI: 10.1046/j.1523-1755.2003.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous maxacalcitol injection therapy regresses hyperplasia of parathyroid and induces apoptosis in uremia

Abstract: PMIT is effective and safe for the treatment of refractory SHPT, and a locally high level of OCT suppresses PTH secretion and regresses parathyroid hyperplasia, which is involved in the induction of apoptosis of parathyroid cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 27 publications
(30 reference statements)
1
42
0
1
Order By: Relevance
“…It is possible for PTx-AT and percutaneous ethanol injection therapy to decrease the number of PTC that over-synthesize and secrete PTH. Moreover, we previously reported that percutaneous maxacalcitol injection therapy (PMIT) induces apoptosis in PTC and reduces the ultrasonographic PTG volume (10). However, regarding clinical investigations, more invasive examinations are difficult, and the development of direct injection into rat PTG enables further elucidation of these biochemical and cellular effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible for PTx-AT and percutaneous ethanol injection therapy to decrease the number of PTC that over-synthesize and secrete PTH. Moreover, we previously reported that percutaneous maxacalcitol injection therapy (PMIT) induces apoptosis in PTC and reduces the ultrasonographic PTG volume (10). However, regarding clinical investigations, more invasive examinations are difficult, and the development of direct injection into rat PTG enables further elucidation of these biochemical and cellular effects.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent intravenous administration of OCT maintained the reduction in serum iPTH level for 4 wk after DI-OCT in u-rats (data not shown). Moreover, we previously reported the maintenance of this decreased level for Ͼ12 wk after PMIT in a clinical investigation (10). The biologic response to medical treatments such as VD that leads to the suppression of PTH synthesis and PTC proliferation is mediated via VDR and CaSR in target cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively to surgery, ultrasound-guided percutaneous fine-needle ethanol injection into nodular hyperplastic parathyroid glands is very common in Japan (Giangrande et al, 1992;Kitaoka et al, 1994;Fukagawa et al, 1999). Apart from ethanol, also calcitriol or novel VDRA can be directly placed into enlarged parathyroid glands using the same technique (Shiizaki et al, 2003). To date no specific guidelines considering sHPT treatment in hemodialysis patients on kidney transplant waiting list have been established.…”
Section: Parathyroidectomymentioning
confidence: 99%